1994
DOI: 10.1103/physrevc.50.733
|View full text |Cite
|
Sign up to set email alerts
|

Directional correlation of γ transitions inGe72following the decay ofGa<

Abstract: Directional correlations of coincident gamma transitions in Ge have been measured following the P decay of Ga (T~y2 --14.1 h), using a spectrom'eter consisting of a Ge(Li) and a Ge detector. The measurements were carried out for 16 gamma cascades populated in Ge, three of which measured for the first time. The results permitted definite spin assignments to the levels at 3325 keV (3 ) and 3342 keV (2 ). In addition, several previous spin assignments to other levels in " Ge were confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Therefore their structure may be described by vibrational models, at least in the low energy region. However many experiments and theoretical work found that the low lying level structure of those nuclei is not a simple vibrator [18][19][20][21] . As a typical isotope in this area, the Ge isotopes present a useful testing ground for nuclear structure calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore their structure may be described by vibrational models, at least in the low energy region. However many experiments and theoretical work found that the low lying level structure of those nuclei is not a simple vibrator [18][19][20][21] . As a typical isotope in this area, the Ge isotopes present a useful testing ground for nuclear structure calculations.…”
Section: Introductionmentioning
confidence: 99%